Comparison of Classroom-Based Sedentary Time and Physical Activity in Conventional Classrooms and Open Learning Spaces Among Elementary School Students - Hartikainen, Jani; Haapala, Eero A.; Poikkeus, Anna-Maija; Lapinkero, Eero; Pesola, Arto J.; Rantalainen, Timo; Sääkslahti, Arja; Gao, Ying; Finni, Taija (Frontiers in Sports and Active Living, 2021)
European children and adolescents spend most of their daily life and especially their school hours being sedentary which may increase their risk for chronic non-communicable diseases later in life. After the curriculum reform of Finnish basic education in 2014, most of the new or renovated comprehensive schools in Finland incorporate open and flexible classroom designs. Their open learning spaces may provide students opportunities to reduce sedentary behavior during school hours. Thus, waist-worn accelerometers were used to assess classroom-based sedentary time (ST), the number of breaks from sedentary time (BST), and physical activity (PA) among cross-sectional samples of 3rd and 5th -grade students during two separate academic years in a school that underwent a renovation from conventional classrooms to open learning spaces. The cohort of 5th grade students before renovation had a smaller proportion of ST from total classroom time (56.97 ± 12.24%, n=42 vs. 67.68 ± 5.61%, n=28, mean difference = 10.71%-points, 95%CI = -15.65 to -5.77, p<.001), a greater number of BST per 60 minutes of classroom time (7.41 ± 1.16 breaks/h vs. 9.19 ± 1.59 breaks/h, mean difference = - 1.78 breaks/h, 95% CI = -2.486 to -1.079, p<.001) and a greater proportion of light intensity PA (28.66 ± 9.99% vs. 22.56 ± 4.59%, mean difference = 6.10%, 95%CI = 2.56 to 9.64, p=.001) than the 5th grade cohort assessed after renovation. The cohort of 3rd grade student had a greater proportion of moderate-to-vigorous intensity PA (MVPA) after the renovation compared to the cohort assessed before the renovation (Mean Rank (Before) =27.22, Mean Rank (After) = 37.58, U =524.0, p=.033). Despite the greater ST found in 5th graders, schools with open learning spaces may facilitate BST or MVPA as observed in the 5th and 3rd grade cohorts in OLS compared to the cohorts in conventional classrooms, respectively. Future studies should seek to investigate and develop teacher practices to capitalize the potential of open classrooms to reduce ST, since classroom renovation alone may not be a sufficient intervention as of itself. Longitudinal studies utilizing randomized controlled trials are warranted.